High-Throughput Silencing Using the CRISPR-Cas9 System: A Review of the Benefits and Challenges. (September 2015) - Wade, Mark
The clustered regularly interspaced short palindromic repeats (CRISPR)/Cas system has been seized upon with a fervor enjoyed previously by small interfering RNA (siRNA) and short hairpin RNA (shRNA) technologies and has enormous potential for high-throughput functional genomics studies. The decision to use this approach must be balanced with respect to adoption of existing platforms versus awaiting the development of more "mature" next-generation systems. Here, experience from siRNA and shRNA screening plays an important role, as issues such as targeting efficiency, pooling strategies, and off-target effects with those technologies are already framing debates in the CRISPR field. CRISPR/Cas can be exploited not only to knockout genes but also to up- or down-regulate gene transcription—in some cases in a multiplex fashion. This provides a powerful tool for studying the interaction among multiple signaling cascades in the same genetic background. Furthermore, the documented success of CRISPR/Cas-mediated gene correction (or the corollary, introduction of disease-specific mutations) provides proof of concept for the rapid generation of isogenic cell lines for high-throughput screening. In this review, the advantages and limitations of CRISPR/Cas are discussed and current and future applications are highlighted. It is envisaged that complementarities between CRISPR, siRNA, and shRNA will ensure that all three technologies remain critical to the success of future functional genomics projects.